Technological mediation, mediating morality and moral imaginaries of design: Performance measurement systems in the pharmaceutical industry - Bottausci, Chiara; Robson, Keith; Dambrin, Claire (Accounting, Organizations and Society, 2024)
In this paper, we seek to understand the ethics of accounting technology design. We commence by working with the concept of technological mediation, which is theorizing how technologies steer actions by evoking given behaviours and by contributing to perceptions and interpretations of reality that form the basis for choices and decisions to act. As such, this relation between people and technologies has important ethical consequences since it implies that technologies contribute actively to how humans do ethics. In this paper, we draw upon a postphenomenological approach (Ihde; Verbeek) to study and to theorise the moral mediations brought about by accounting technology, by examining how, in its design , technology can actively mediate the moral choices and guide the moral actions human beings make. Our central research question is ‘how is morality mediated in the design of accounting technologies?‘. This question is explored through an ethnographic study of the design of a new Performance Measurement and Compensation System in the Italian division of a multi-national pharmaceutical company. We offer two main contributions towards answering this question. First, by working within the theory of technological mediation, we develop the concept of a ‘moral imaginary’ as an approach to understanding designing the morality of things. Second, we elaborate a process model to theorise how moral mediations unfold in the design of accounting technology. From our conceptual motivation and the theoretical elaboration it inspired, we illuminate how the design of accounting technologies, in this case a PMS system, is a form of ‘engineering ethics’ through techno-moral mediation.